2022
DOI: 10.1186/s12977-022-00600-9
|View full text |Cite
|
Sign up to set email alerts
|

Repression of HIV-1 reactivation mediated by CRISPR/dCas9-KRAB in lymphoid and myeloid cell models

Abstract: Background Despite antiretroviral treatment efficacy, it does not lead to the complete eradication of HIV infection. Consequently, reactivation of the virus from latently infected cell reservoirs is a major challenge toward cure efforts. Two strategies targeting viral latency are currently under investigation: the “shock and kill” and the “block and lock.” The “Block and Lock” methodology aims to control HIV-1 latency reactivation, promoting a functional cure. We utilized the CRISPR/dCas9-KRAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…These positive results prompted a clinical trial, which is currently ongoing (NCT05144386). Several studies have evaluated the applicability of catalytically inactive Cas9 to reactivate or silence HIV and SIV transcription [114,[121][122][123][124][125][126][127][128], but all these studies are still in the pre-clinical stage.…”
Section: Genetic and Epigenetic Modulation To Impact Hiv Transcriptionmentioning
confidence: 99%
“…These positive results prompted a clinical trial, which is currently ongoing (NCT05144386). Several studies have evaluated the applicability of catalytically inactive Cas9 to reactivate or silence HIV and SIV transcription [114,[121][122][123][124][125][126][127][128], but all these studies are still in the pre-clinical stage.…”
Section: Genetic and Epigenetic Modulation To Impact Hiv Transcriptionmentioning
confidence: 99%
“…Another approach is to promote a permanent latent state by inhibiting HIV-1 transcription factors. In line with the second approach, da Costa et al used sgRNAs targeting the HIV-1 proviral genome (LTR1-LTR5) and CRISPR/dCas9-KRAB to block HIV-1 reactivation in latently infected T cells and myeloid cells treated with latency-reversing agents such as PKC agonists and HDAC inhibitors [ 208 ]. They found that targeting the LTR enhancer region provided the best repression, and one of their CRISPR constructs inhibited latency reactivation by 160×.…”
Section: Crispr and Gene Regulationmentioning
confidence: 99%